La antropología - Dannemann, Manuel; Munizaga, Carlos (Revista Chilena de Humanidades, 2015)
This paper deals with the relationship between anthropology and other sciences, and the why and wherefore of its acquiring an autonomous character within the field of investigations on human behaviour. There is a de scription of the various areas included in General Anthropology, as wel! as of the main trends of anthrop8lo gical thought and th eir projections in Chile. The authors then summarize the pragmatical importance of this science in the development of societies.